The Success Factors of Tourist Destination: A Study of Cibeureum Coffee Village (Ccv), Kuningan District, West Java - Suryono, Chondro; Setiawati, Ety; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
The internal and external environment has been identified as the main factor that would increase the number of tourists in visiting the desired destination. Cibeureum Coffee Village (CCV) had the specialty and the uniqueness to be offered to the potential visitors. Hence, this research proved that without good promotional strategy, the number of visitors would be affected tremendously. Thus, this research identifies the factors that affect the decision of the tourist to visit Cibeureum Coffee Village, Kuningan Regency, West Java, Indonesia. The three factors found in this research are individual factor, environment and psychological factors. Tourism is one of the most strategic sectors in Kuningan Regency, considering that there are many natural resources that are well known and well-managed. Apart from nature tourism, there are also cultural, historical tourism such as the Linggarjati Meeting House and other artificial tours. This research also found that other areas needs to be analyzed by the management based on the internal and external environment. Hence, this research also proved that the internal factors must be taken into consideration in enhancing the numbers of tourist to CCV.